Cell cycle arrest in the jewel wasp Nasonia vitripennis in larval diapause. (April 2018) - Shimizu, Yuta; Mukai, Ayumu; Goto, Shin G.
Graphical abstract: Highlights: Developmental and cell cycle arrests occur in diapause larvae of the jewel wasp. Cell cycle arrest occurs primarily in G0/G1 and secondarily in G2. Downregulation of housekeeping genes and cell cycle regulatory genes is evident. Abstract: Insects enter diapause to synchronise their life cycle with biotic and abiotic environmental conditions favourable for their development, reproduction, and survival. One of the most noticeable characteristics of diapause is the blockage of ontogeny. Although this blockage should occur with the cessation of cellular proliferation, i.e. cell cycle arrest, it was confirmed only in a few insect species and information on the molecular pathways involved in cell cycle arrest is limited. In the present study, we investigated developmental and cell cycle arrest in diapause larvae of the jewel wasp Nasonia vitripennis. Developmental and cell cycle arrest occur in the early fourth instar larval stage of N. vitripennis under short days. By entering diapause, the S fraction of the cell cycle disappears and approximately 80% and 20% of cells arrest their cell cycle in the G0/G1 and G2 phases, respectively. We further investigated expression of cell cycle regulatory genes and some housekeeping genes to dissect molecular mechanisms underlying the cell cycle arrest.